Pengaruh Modernisasi Administrasi Perpajakan Terhadap Kepatuhan Wajib Pajak Badan - Siti Mialasmaya (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2019)
Modernization of tax administration as one of the improvements for the administration performance, conducted in personally, team, or group to get the efficiency, economic, and the suitable improvement. This research aimed to know about the effects of modernization of tax administration of the obedience of the people in Tax Service Office Pratama Bandung Cibeunying. The method of this research employs the Verifikative descriptive. The result of the research show that the analysis of product moment is 0,802, which mean consisting the relation between modernization of tax administration and the people. The result of the coefficient of determination analysis shows the number 65%, which mean the modernization of tax administration influenced 65% towards the people. Moreover, the 35% is the other effects of beyond the variable which are not talked in this research.